WHO Dengue Case Classification 2009 and its usefulness in practice: an expert consensus in the Americas - Horstick, Olaf; Martinez, Eric; Guzman, Maria Guadalupe; Martin, Jose Luis San; Runge-Ranzinger, Silvia (Pathogens and global health, 2015)
Introduction:In 2009, the new World Health Organization (WHO) dengue case classification - dengue/severe dengue (D/SD) - was introduced, replacing the 1997 WHO dengue case classification: dengue fever/dengue haemorrhagic fever/dengue shock syndrome (DF/DHF/DSS).Methods:A 2-day expert consensus meeting in La Habana/Cuba aimed to (1) share the experiences from Pan American Health Organization (PAHO) member states when applying D/SD, (2) present national and local data using D/SD, and (3) agree with the presented evidence on a list of recommendations for or against the use of D/SD for PAHO, and also globally.Results:Eight key questions were discussed, concluding: (1) D/SD is useful describing disease progression because it considers the dynamic nature of the disease, (2) D/SD helps defining dengue cases correctly for clinical studies, because it defines more precisely disease severity and allows evaluating dynamically the progression of cases, (3) D/SD describes correctly all clinical forms of severe dengue. Further standards need to be developed regionally, especially related to severe organ involvement, (4) D/SD allows for pathophysiological research identifying - in a sequential manner - the clinical manifestations of dengue related to pathophysiological events, (5) the warning signs help identifying early cases at risk of shock (children and adults), pathophysiology of the warning signs deserves further studies, (6) D/SD helps treating individual dengue cases and also the reorganization of health-care services for outbreak management, (7) D/SD helps diagnosing dengue, in presumptive diagnosis and follow-up of the disease, because of its high sensitivity and high negative predictive value (NPV), and (8) there is currently no update of the International Disease Classification10 (ICD10) to include the new classification of dengue (D/SD); therefore, there are not enough experiences of epidemiological reporting. Once D/SD has been implemented in epidemiological surveillance, D/SD allows to (1) identify severity of dengue cases in real time, for any decision-making on actions, (2) measure and compare morbidity and mortality in countries, and also globally, and (3) trigger contingency plans early, not only based on the number of reported cases but also on the reported severity of cases.Conclusion:The expert panel recommends to (1) update ICD10, (2) include D/SD in country epidemiological reports, and (3) implement studies improving sensitivity/specificity of the dengue case definition.